Risk factors for relapse of chronic pulmonary aspergillosis after discontinuation of antifungal therapy. (April 2020) - Bongomin, Felix; Otu, Akaninyene; Harris, Chris; Foden, Philip; Kosmidis, Chris; Denning, David W.
Abstract: Objectives: We aimed to identify the frequency and risk factors for disease relapse following cessation of antifungal therapy in CPA. Methods: This retrospective audit at the National Aspergillosis Centre, Manchester, UK assessed outcomes for patients with CPA who had received antifungal treatment and for whom therapy was discontinued for at least one month between August 2009 and May 2017. We defined relapse as a deterioration in two of the following parameters: clinical, radiological, serological or sputum microbiological markers of CPA activity. Results: Therapy was discontinued in 102 patients. Age distribution was 63.7 ± 11.5 years. Therapy was recommenced in 43 (42%) patients of whom 21 met our definition of relapse — 31% of those with bilateral and 11% of those with unilateral disease. Patients with bilateral disease and those with ≥ 1 aspergillomas were more likely to relapse on univariate analysis. In a multivariable logistic regression analysis, bilateral disease was the only independent risk factor for relapse (OR: 3.0; 95% CI: 1.0–8.8; p = .044). Conclusions: Bilateral CPA is a risk factor for relapse after treatment discontinuation. A longer duration of treatment may be associated with a lower rate of relapse in extensive CPA, whereas more limited disease may respond to shorter courses. Highlights: Relapse is problematic in chronic pulmonary aspergillosis (CPA) following discontinuation of triazole maintenance therapy We defined relapse as a deterioration in two of the following parameters: clinical, radiological, serological or sputum microbiological markers of CPA activity. Patients with bilateral chronic pulmonary aspergillosis are three times more likely to relapse after treatment discontinuation compared to those with unilateral disease. A longer duration of treatment, e.g. 24 months, may be associated with a lower rate of relapse in extensive CPA, whereas more limited disease may respond to shorter courses.